Pengaruh Lingkungan Kerja Fisik dan Non-Fisik terhadap Kebosanan Kerja karyawan di Akademi Maritim Yogyakarta (AMY) - Himawan Aditya Pratama (Sekolah Tinggi Maritim Yogyakarta, 2019)
This study aims to describe and explain the physical or non-physical work environment of one of the educational institutions in Yogyakarta provided at the Yogyakarta Maritime Academy (AMY). The type of research used in this study is exploration research. The population in this study were all permanent employees who gathered 40 people. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis, inferential statistical analysis used in this study is multiple linear regression analysis. The results showed that both physical and non-physical work environments were positively and significantly related to employee work boredom at the Yogyakarta Maritime Academy.